Leukocyte Trafficking and Hemostasis in the Mouse Fetus in vivo: A Practical Guide - Margraf, Andreas; Sperandio, Markus (Frontiers in Cell and Developmental Biology, 2021)
In vivo observations of blood cells and organ compartments within the fetal mammalian organism are difficult to obtain. This practical guide describes a mouse model for in vivo observation of the fetal yolk-sac and corporal microvasculature throughout murine gestation, including imaging of various organ compartments, microvascular injection procedures, different methods for staining of blood plasma, vessel wall and circulating cell subsets. Following anesthesia of pregnant mice, the maternal abdominal cavity is opened, the uterus horn exteriorized, and the fetus prepared for imaging while still connected to the placenta. Microinjection methods allow delivery of substances directly into the fetal circulation, while substances crossing the placenta can be easily administered via the maternal circulation. Small volume blood sample collection allows for further in vitro workup of obtained results. The model permits observation of leukocyte-endothelial interactions, hematopoietic niche localization, platelet function, endothelial permeability studies, and hemodynamic changes in the mouse fetus, using appropriate strains of fluorescent protein expressing reporter mice and various sophisticated intravital microscopy techniques. Our practical guide is of interest to basic physiologists, developmental biologists, cardiologists, and translational neonatologists and reaches out to scientists focusing on the origin and regulation of hematopoietic niches, thrombopoiesis and macrophage heterogeneity.